Potential diagnostic markers and therapeutic targets for rheumatoid arthritis with comorbid depression based on bioinformatics analysis - Zhou, Tao-tao; Sun, Ji-jia; Tang, Li-dong; Yuan, Ying; Wang, Jian-ying; Zhang, Lei (Frontiers in Immunology, 2023)
Rheumatoid arthritis (RA) and depression are prevalent diseases that have a negative impact on the quality of life and place a significant economic burden on society. There is increasing evidence that the two diseases are closely related, which could make the disease outcomes worse. In this study, we aimed to identify diagnostic markers and analyzed the therapeutic potential of key genes.